Get ready! for standardized tests. Grade two / Math - Swanson, Kristin B. (New York : McGraw-Hill, 2001)
Offers advice to parents on how to prepare their second graders to take the math portion of standardized tests, featuring study tips, test-taking strategies, subject reviews, practice exercises, and sample exams with answers.
"Real sample test"--Cover.
Cover title: Get ready! for standardized tests.
Includes bibliographical references (p. 77).
Professional
Keywords: Achievement tests -- United States -- Study guides; Mathematics -- Study and teaching (Elementary) -- United States; Mathematics -- Study and teaching -- Parent participation -- United States; Achievement tests -- United States -- Study guides; Mathematics -- United Sates -- Examinations -- Study guides; Mathematics -- United States -- Study and teaching